Huge Avenues of Opportunities (With Some Potholes) Opened by the Very Small Things - Luna Criado, Carlos (2014)
In its incessant exploration of the cosmos into the cosmos, crossing the dimensionality barrier, science is living a unique moment with an unstoppable knowledge growth ranging from the subtle details of the immensity to the vastness of the very small. In the last aspect, progress is now incredible extremely rapid, and today, shape the matter at nanoscale to prepare engineered low dimensional systems (thin films, elongated nanostructures and nanocrystals and quantum dots) is an everyday reality common throughout the world. Nanoscopic objects with an increasing (and sometimes funny) variety of sizes and forms, including ...